MORTALIDADE DE ð˜ˆð˜¯ð˜µð˜ªð˜¤ð˜¢ð˜³ð˜´ð˜ªð˜¢ ð˜¨ð˜¦ð˜®ð˜®ð˜¢ð˜µð˜¢ð˜ð˜ªð˜´ HÃœBNER, 1818 (LEPIDOPTERA, NOCTUIDAE) POR ð˜•ð˜°ð˜®ð˜¶ð˜³ð˜¢ð˜¦ð˜¢ ð˜³ð˜ªð˜ð˜¦ð˜ºð˜ª (FARLOW) SAMSON EM LAVOURAS DE SOJA NO PARANÃ, BRASIL - Santos, Benedito Baptista dos (REVISTA DE AGRICULTURA, 2020)
MORTALIDADE DE ð˜ˆð˜¯ð˜µð˜ªð˜¤ð˜¢ð˜³ð˜´ð˜ªð˜¢ ð˜¨ð˜¦ð˜®ð˜®ð˜¢ð˜µð˜¢ð˜ð˜ªð˜´ HÃœBNER, 1818 (LEPIDOPTERA, NOCTUIDAE) POR ð˜•ð˜°ð˜®ð˜¶ð˜³ð˜¢ð˜¦ð˜¢ ð˜³ð˜ªð˜ð˜¦ð˜ºð˜ª (FARLOW) SAMSON EM LAVOURAS DE SOJA NO PARANÃ, BRASIL